The Macroeconomics of Share Prices in the Medium Term and in the Long Run - Jakob B. Madsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
This paper develops a macro-model of share prices that predicts that the growth rates in real share prices and real dividends gravitate toward predictable constants in the long run, but fluctuate on approximately decennial frequencies due to movements in capitals share in total income and the output-capital ratio. The model has important implications for medium-term and long-run movements in real share prices and dividends, required share returns, the effects of new technologies on share returns, share price valuation, and whether shares are less risky in the long run than in the short run. Using macroeconomic data over 130 years for 22 OECD countries, the data give support for the model.
Keywords: E44; G12; 330; share prices and dividends in the long run; share valuation; required share returns; macroeconomic factors; Kapitalertragsteuer; Dividende; Zeitreihenanalyse